Skilful reflection as an epistemic virtue - MI, Chienkuo (Institutional Knowledge at Singapore Management University, 2015)
This paper advances the claim that skilful reflection is a master virtue in that skilful reflection shapes and corrects the other epistemic and intellectual virtues. We make the case that skilful reflection does this with both competence-based epistemic virtues and character-based intellectual virtues. In making the case that skilful reflection is a master virtue, we identify the roots of ideas central to our thesis in Confucian philosophy. In particular, we discuss the Confucian conception of reflection, as well as different levels of epistemic virtue. Next we set out the Dual Process Hypothesis of Reflection, which provides an explanation of the workings of reflection in relation to Type 1 and Type 2 cognitive processes. In particular, we flag how repetition of Type 2 processes may eventually shape Type 1 processes and produce what we call downstream reflection. We distinguish competence-based epistemic virtues from character-based intellectual virtues. We also explain how our metacognition account of reflection, drawing on a Confucian conception of reflection and the Dual Process Hypothesis of Reflection, explains skilful reflection as a master virtue. Finally we outline an application of our metacognition account of reflection to a current debate in epistemology.